Correlation between PTSD and sleep quality in community-dwelling elderly adults in Hunan province of China - Cao, Jiri; Zhou, Yang; Su, Man-Man; Chen, Wen-Hui (Frontiers in Psychiatry, 2022)
Abstract Objective: To understand the occurrence of post-traumatic stress disorder (PTSD) and the current status of sleep quality among community-dwelling elderly adults in Hunan Province of China, to explore the correlation between the two, and to analyze the trend of sleep disorders in PTSD elderly adults . Methods: A random sample containing 1173 community-dwelling elderly adults in Hunan Province was established between March and May 2022, and an on-site face-to-face survey was administered using the PTSD Checklist – Civilian Version (PCL-C) with good reliability and validity, the Pittsburgh Sleep Quality Index (PSQI) scale, and a self-designed general condition questionnaire. Results: The incidence of PTSD in the 1173 participants was 14.3% (168/1173). The total incidence of sleep disorders was 40.9% (480/1173); more specifically, the incidence of sleep disorders in participants with no PTSD symptom, in participants with mild-to-moderate PTSD symptoms, and in participants with severe PTSD symptoms was 36.3%, 69.8% and 66.7%, respectively. The Spearman’s rank correlation analysis showed that the total PTSD score and the scores of each dimension (i.e., re-experiencing symptom cluster, avoidance symptom cluster and hypervigilance symptom cluster) were positively correlated with the total PSQI score and its dimension scores (i.e., sleep quality, time to fall asleep, sleep duration, sleep efficiency, sleep disturbance, hypnotic medication, and daytime function) (P < 0.05). The correlation coefficients ranged from 0.013 to 0.495. For all PSQI dimensions, the differences across participants with different degrees of PTSD were statistically significant (P<0.05). Conclusions: The overall status of PTSD and sleep quality in community-dwelling elderly adults in Hunan Province was not optimistic. The elderly with PTSD were more prone to sleep disorders, and the more severe the symptoms of PTSD, the poorer the sleep quality was. However, differences were observed in the scores of each dimension of sleep across participants with different degrees of PTSD. Regardless of the degree of PTSD symptoms, the sleep quality of the elderly is severely affected, and the occurrence rate is not unlimited.